Number of Positive Lymph Nodes Is Superior to LNR and LODDS for Predicting the Prognosis of Pancreatic Neuroendocrine Neoplasms - Gao, Bingqiang; Zhou, Dongkai; Qian, Xiaohui; Jiang, Yuancong; Liu, Zhenghao; Zhang, Wang; Wang, Weilin (Frontiers in Endocrinology, 2021)
Background: The American Joint Committee on Cancer (AJCC) staging for pancreatic neuroendocrine neoplasms (PanNENs) based on the number of positive lymph nodes (PLNs) is the most widely accepted nodal staging system. New nodal staging schemes that take both the number of PLNs and the number of examined lymph nodes into consideration have emerged as useful prognostic tools. The aim of the current study was to determine the most effective nodal staging system, among the 8th edition AJCC N staging (or PLN staging), lymph node ratio (LNR), and log odds of positive lymph nodes (LODDS), for predicting the cause-specific survival of patients with PanNENs. Methods: The clinicopathological and prognostic data of 2,295 patients from the Surveillance, Epidemiology, and End Results (SEER) database, diagnosed with PanNENs between 1988–2015, were reviewed retrospectively. Results: A multivariate analysis identified PLN and LNR staging as independent prognostic factors, but not LODDS. The PLN staging exhibited higher C-index and area under the curve values than those of the LNR and LODDS, indicating better predictive discriminatory capacity. No significant difference in the survival of patients was observed within the same PLN staging subgroup according to the number (high or low) of examined lymph nodes. In contrast, intra-group heterogeneity was seen with use of LNR and LODDS staging, due to overestimation of the risk of insufficient examined lymph nodes. And LODDS failed to stratify patients without lymph nodes metastasis into different risk groups. Conclusions: The PLN staging is more reliable than LNR and LODDS staging for predicting the cause-specific survival of PanNENs.